Protective Effects of Ruta Chalepensis L. (Rutacae) Oil Extract Against Potassium Bromate Induced Nephrotoxicity in Male Rats: Histopathological Study - Eldurssi, Ibrahim S.; MM, Ebtesam; Gheth, Gasem MA; Abdalla, Abdullah AH; Algassi, Mabroka A (Asian Journal of Pharmaceutical Research and Development, 2019)
Ruta chalepensis L. (Rutaceae) is a perennial herb, widely distributed in the Mediterranean area, with glabrous stem, alternate bipinnatisect leaves. It is an ancient medicinal plant still being used in the traditional medicine of many countries. Potassium bromate (KBrO3) is a strong oxidizing agent that has been used in flour milling, as a cheese making, in beer malting, as a component of cold hair-wave liquids. This study studies the protective and curative effects of R. chalepensis oil extract against KBrO3 toxicity on kidney of male rats. Accordingly, a total number of fifty male albino rats were divided into five groups. The first group served as a control animals. The second group was administered Rue at an oral daily dose of 0.5 g/Animal for four weeks. The third group received KBrO3 100 mg/kg/b. w. for four weeks. The fourth group (protective group) was initially administered with Rue alone for 2 weeks and followed by KBrO3 in association with Rue for 2 weeks. The fifth group (therapeutic group) was first given KBrO3 alone for 2 weeks and was secondly administered Rue in association with KBrO3 for 2 weeks. At the end of 2nd and 4th weeks of treatment, the kidney tissues were collected for histopathological studies. Histopathological studies revealed that the renal reactions of rats from the Rue group showed normal architecture pattern same that observations as in the control rats. The rats treated with KBrO3 showed vacuolation and contraction of glomerular tuft, separation in intertubular connective tissue, necrotic changes in some areas and hyaline changes in tubules. Furthermore, lymphoid infiltration and intratubular hemorrhage, dilated in tubules with loss of cellular boundary. In the protective group minimal changes in the structure of the kidney was revealed compared to control. Both glomeruli and convoluted tubules gained the normal features. In therapeutic group, renal sections revealed improvement in the histological structure though there was a mild necrosis and slight in inflammatory leucocytic infiltration. The results of this study suggest the nephrotoxic effect of KBrO3 and the ameliorative effect of Rue when administrated for protective and therapeutic purposes.